Socioeconomic impacts of longhouse tourism on local communities : a case study of selected longhouse communities in the Ai, Engkari and Skrang river systems, Sri Aman Division, Sarawak - Benji, Anak Jihen (Universiti Malaysia Sarawak (UNIMAS), 2001)
Sarawak, is popular for its ethnic and cultural diversity, especially among Dayaks, One of the prominent features of the Dayak culture is community living in longhouses. Among the major ethnic groups of the Dayak is the Iban who commonly live in longhouses on riverbanks, practicing shifting rice cultivation and are still following customary beliefs and practices.